Application of “smart” amine donors for rapid screening and scale-up of transaminase-mediated biotransformations - Gomm, Andrew; Grigoriou, Stylianos; Peel, Christopher; Ryan, James; Mujtaba, Nafees; Clarke, Thomas; Kulcinskaja, Evelina; O'Reilly, Elaine (Wiley, 2018)
The “smart” amine donors o‐xylylenediamine and cadaverine were employed for the rapid screening of a large ketone library and subsequent preparative‐scale synthesis of selected compounds using a commercially available amine transaminase, ATA256. The methodology enables both screening and preparative‐scale biotransformations to be performed with a single enzyme and simplifies the generation of sp3‐rich small‐molecule libraries.